Developing core sets for patients with obstetricbrachial plexus injury based on the International Classificationof Functioning, Disability and Health. Issue 6 (June 2013) - Duijnisveld, B. J.; Saraç, Ç.; Malessy, M. J. A.; Brachial Plexus Advisory Board, The ICF; Vliet Vlieland, T. P. M.; Nelissen, R. G. H. H.
Abstract : Background: Symptoms of obstetric brachial plexus injury (OBPI) vary widely over the course of time and from individual to individual and can include various degrees of denervation, muscle weakness, contractures, bone deformities and functional limitations. To date, no universally accepted overall framework is available to assess the outcome of patients with OBPI. The objective of this paper is to outline the proposed process for the development of International Classification of Functioning, Disability and Health (ICF) Core Sets for patients with an OBPI. Methods: The first step is to conduct four preparatory studies to identify ICF categories important for OBPI: a) a systematic literature review to identify outcome measures, b) a qualitative study using focus groups, c) an expert survey and d) a cross-sectional, multicentre study. A first version of ICF Core Sets will be defined at a consensus conference, which will integrate the evidence from the preparatory studies. In a second step, field-testing among patients will validate this first version of Core Sets for OBPI. Discussion: The proposed method to develop ICF Core Sets for OBPI yields a practical tool for multiple purposes: for clinicians to systematically assess and evaluate the individual's functioning, for researchers to design and compare studies, and for patients to get more insight into their health problems and their management.